Compton scattering geometry: a tool to study radiation interaction characteristics of rare earth compounds doped in low-Z organic compound - Singh, Mohinder; Tondon, Akash; Sandhu, Balvir S.; Singh, Bhajan (Radiochimica acta, 2023)
The present measurements comprise of Compton scattering technique at six energies from 0.242 MeV to 0.402 MeV (not available from conventional radioisotopes) by scattering of primary gamma photon beam of 0.662 MeV energy from cylindrical aluminium target at different scattering angles. Two inorganic (rare-earth) compounds, Lanthanum (3+) nitrate hexahydrate and Samarium (3+) nitrate hexahydrate in a Low- organic solvent (acetone), have shown certain radiation interaction characteristics are the subject of study. The collimated beam of scattered gamma rays impinges on the plastic container having solution of rare earth compounds in the acetone of different concentrations. The transmitted gamma ray beam is detected by a well-collimated 2″ × 2″ NaI(Tl) scintillation detector and is analysed by a PC-based ORTEC Mastero-32 MCA. Attenuation coefficients along with some shielding parameters i.e. molar extinction coefficients, half value layer, tenth value layer and mean free path are evaluated. Besides this, Computed Tomography numbers and photon interaction cross-sections (photoelectric, coherent and incoherent) are also determined. The measured values of these parameters are compared with WinXCom software package’s values and are found to be in good agreement. The available data on rare earth salts’ solutions, in the current measurements, is scientifically important in nuclear and radiation physics, bridging the gap in which radiation workers do not have access to such data.